2013
DOI: 10.1002/pros.22740
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of human prostate cancer cells with tumor initiating properties in mouse and zebrafish xenografts by differential adhesion

Abstract: BACKGROUND Prostate tumor-initiating cells (TICs) have intrinsic resistance to current therapies. TICs are commonly isolated by cell sorting or dye exclusion, however, isolating TICs from limited primary prostate cancer (PCa) tissues is inherently inefficient. We adapted the collagen adherence feature to develop a combined immunophenotypic and time-of-adherence assay to identify human prostate TICs. METHODS PCa cells from multiple cell lines and primary tissues were allowed to adhere to several matrix molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 53 publications
1
63
0
Order By: Relevance
“…The extra-uterine development of hundreds of eggs also permits a greater number of studies in genetically identical organisms. Since the first reported xenotransplantation of human cells into zebrafish ( Lee et al , 2005), many laboratories have shown that zebrafish embryos are useful for the study of other facets of tumour biology including cancer-induced angiogenesis ( Haldi et al , 2006); cancer cell invasion and metastasis ( de Boeck et al , 2016; Marques et al , 2009); cancer stem cell growth ( Bansal et al , 2014; Chen et al , 2017); interaction of cancer cells with the host ( Feng & Martin, 2015); and drug screening ( Corkery et al , 2011; Gibert et al , 2013). Importantly, the development of human tumours and their response to chemotherapeutic treatment in zebrafish embryos is comparable to that observed in mouse xenograft assays ( Fior et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The extra-uterine development of hundreds of eggs also permits a greater number of studies in genetically identical organisms. Since the first reported xenotransplantation of human cells into zebrafish ( Lee et al , 2005), many laboratories have shown that zebrafish embryos are useful for the study of other facets of tumour biology including cancer-induced angiogenesis ( Haldi et al , 2006); cancer cell invasion and metastasis ( de Boeck et al , 2016; Marques et al , 2009); cancer stem cell growth ( Bansal et al , 2014; Chen et al , 2017); interaction of cancer cells with the host ( Feng & Martin, 2015); and drug screening ( Corkery et al , 2011; Gibert et al , 2013). Importantly, the development of human tumours and their response to chemotherapeutic treatment in zebrafish embryos is comparable to that observed in mouse xenograft assays ( Fior et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we developed a surrogate self-renewal assay that allowed us to isolate TICs from PCa tissue based on α2β1-integrin (also called CD49b/CD29) and CD44 protein expression (6). Herein, we demonstrate that in prostate TICs, BMI-1 is overexpressed and functionally regulates their survival and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Bansal et al isolated prostate TICs from other cancer cells by allowing them to bind to collagen-coated surfaces for a short period of time. They found that TICs bound faster, and by washing away other cells, cancer cells with stem-like properties could be enriched [103]. Zhang et al applied the same idea in a more controlled manner to isolate breast cancer TICs.…”
Section: Methods Of Tic Purificationmentioning
confidence: 99%